Effects on Personal Factors Through Flipped Learning and Gamification as Combined Methodologies in Secondary Education - Segura-Robles, Adrián; Fuentes-Cabrera, Arturo; Parra-González, María Elena; López-Belmonte, Jesús (Frontiers in Psychology, 2020)
Purpose This study aims to analyze the effects of a flipped and gamified program on the autonomy, competence, relation with others, satisfaction/enjoyment, intrinsic and extrinsic motivation, and boredom of students of Physical Education. Method The study used a control group and an experimental group to compare pretest and posttest data in both of them. Instruments used were the Basic Psychological Needs in Exercise Scale, Sport Motivation Scale, and Sport Satisfaction Instrument, all of them validated in academic literature. Results On one hand, data indicated that autonomy has been increased with the application of these teaching methodologies. On the other hand, students’ satisfaction, enjoyment, and intrinsic motivation have improved based on the interaction with gamification and flipped learning. Finally, with all dimensions, it seems that academic performance has been improved, although not in a significative way. Discussion/Conclusion Results of the study provide to educational researchers valuable information for a better understanding of how flipped learning and gamification influence personal performance of Physical Education students.